Isolating membrane, preparation method thereof and electrochemical device

By coating the composite material layer of inorganic binder and inorganic particles on the surface of the main film of the battery isolation film, a "grass-like" structure of needle-shaped, sheet-shaped and spherical crystals is formed, which solves the problem of insufficient heat resistance of the existing isolation film at high temperatures, and realizes the stability and safety of the isolation film at high temperatures.

CN119627361APending Publication Date: 2025-03-14SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411709925.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing battery isolation films are insufficient in heat resistance under high temperature conditions, which easily melts and causes short circuits in the battery, and cannot meet the safety requirements of large-capacity high-energy density electrochemical devices.

Method used

Using a composite material layer including an inorganic binder and inorganic particles, the composite material layer contains crystals formed of an inorganic binder, and the crystals include needle-shaped whiskers, sheet-shaped crystals and spherical crystals, and is prepared by coating the composite material layer slurry on at least one side of the body film and drying.

Benefits of technology

The thermal resistance and mechanical properties of the isolation film are improved, making it stable and lasting under high temperature conditions, ensuring safe and efficient operation of the electrochemical device at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627361A_ABST
    Figure CN119627361A_ABST
Patent Text Reader

Abstract

The invention discloses an isolating membrane, a preparation method thereof and an electrochemical device, and belongs to the technical field of isolating membranes. The isolating membrane comprises a body membrane and a composite material layer arranged on at least one side surface of the body membrane, the composite material layer comprises inorganic particles and an inorganic binder; the inorganic binder comprises an M2O.nSiO2 component and / or aluminum sol with the chemical formula of a (Al2O3.mH2O). BHx.cH2O, M comprises at least one of Na, K and Li, and n is greater than or equal to 1 and less than or equal to 4; al2O3.mH2O is hydrated alumina, and Hx is a peptizing agent. The isolating membrane not only has better peel strength, puncture strength, wettability and air permeability, but also has good ionic conductivity, and can be used more stably and lastingly under a high-temperature condition, so that an electrochemical device containing the isolating membrane can also operate safely and efficiently under the high-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of isolation membranes, and in particular to an isolation membrane and a preparation method thereof and an electrochemical device. Background Art

[0002] Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, electrolyte and separator. The separator is mainly used to separate the positive and negative electrodes of the electrochemical device to prevent direct contact between the positive and negative electrodes, and to provide a transmission channel for lithium ions while blocking the passage of electrons to avoid battery short circuit. The performance of the separator has a great influence on the interface structure and internal resistance of the electrochemical device, and will directly affect the electrochemical performance and safety of the electrochemical device.

[0003] At present, battery separators are usually based on polyethylene (PE) and polypropylene (PP). This type of battery separator has insufficient heat resistance and will soften and deform above 130°C. Under conditions such as overcharge, over-discharge, rapid charge and discharge, abuse or high temperature, the separator is easy to melt and break, resulting in a short circuit in the battery, which leads to thermal runaway, causing the battery to catch fire or even explode, making it difficult to meet the strict safety requirements of large-capacity and high-energy-density electrochemical devices. In addition, polyethylene and polypropylene have low surface energy and poor wettability with electrolytes, resulting in the inability of the separator pores to be completely filled with electrolytes, which will also affect the performance of electrochemical devices.

[0004] Therefore, how to provide an isolation membrane that can effectively suppress the occurrence of thermal runaway and ensure that the electrochemical device can still operate safely and efficiently under high temperature conditions has become a current research hotspot.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide an isolation membrane and a preparation method thereof and an electrochemical device to solve or improve the above technical problems.

[0007] The present invention can be implemented like this:

[0008] In a first aspect, the present invention provides an isolation membrane, the isolation membrane comprising a main body membrane and a composite material layer disposed on at least one side surface of the main body membrane; the composite material layer comprises inorganic particles and an inorganic binder;

[0009] The inorganic binder includes a component with a chemical formula of M2O·nSiO2 and / or a component with a chemical formula of a(Al2O3·mH2O)·bH x ·cH2O aluminum sol, wherein M includes at least one of Na, K and Li, 1≤n≤4; Al2O3·mH2O is hydrated aluminum oxide, H x It is a peptizing agent, and b is smaller than a, c and m.

[0010] In an optional embodiment, the mass of the inorganic binder is 1% to 35% of the mass of the inorganic particles in the composite material layer, preferably 1 to 20%, and more preferably 1 to 12%.

[0011] In an optional embodiment, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the composite material layer.

[0012] In an optional embodiment, the aluminum sol is essentially a colloidal solution of charged aluminum oxide particles uniformly dispersed in water.

[0013] In an optional embodiment, the aluminum sol has at least one of the following characteristics:

[0014] Feature 1: The particle size of aluminum sol ranges from 5nm to 200nm;

[0015] Feature 2: The pH value of aluminum sol is 4 to 10;

[0016] Feature 3: The aluminum sol contains aluminum oxide particles, and the shape of the aluminum oxide particles includes at least one of feather-like, floc-like and fibrous.

[0017] In an optional embodiment, the composite material layer contains crystals formed by an inorganic binder; the crystals include at least needle-shaped whiskers, some of the crystals together form a whisker group, and the remaining crystals are located between the inorganic particles.

[0018] In an optional embodiment, the crystals further include at least one of plate-like crystals and spherical crystals.

[0019] In an optional embodiment, the diameter of the whisker is 40 nm to 900 nm.

[0020] In an alternative embodiment, the longest length of the whisker group is 1 μm to 20 μm.

[0021] In an alternative embodiment, the whisker population is "brush-like".

[0022] In an alternative embodiment, the diameter of the whisker is 50 nm to 600 nm. In an alternative embodiment, the longest length of the whisker group is 5 μm to 11 μm.

[0023] In an optional embodiment, the longest distance between any two points on the surface of the plate-like crystal is 1 μm to 3 μm.

[0024] In an optional embodiment, the longest distance between any two points on the surface of the spherical crystal is 1 μm to 3 μm.

[0025] In an optional embodiment, the inorganic particles have at least one of the following characteristics:

[0026] Feature 4: The inorganic particles include at least one of kaolin, boehmite, clay, molecular sieve, Al2O3, SiO2, BaSO4, BaO, MgO, CuO, LiAlO2, ZrO2, Fe2O3, BaTiO3, α-V2O5, PbTiO3, CaSiO3, titanium dioxide, LiF, MgF2, BaF2, TiB2, Mg(OH)2, MoS2, SiC, Si3N4 and carbon nanotubes; preferably include at least one of boehmite, Al2O3, SiO2 and BaTiO3;

[0027] Feature 5: The average particle size of the inorganic particles is 10 nm to 5 μm, preferably 11 nm to 4.9 μm.

[0028] In an optional embodiment, the thickness of the isolation film is 2.3 μm to 48 μm, preferably 3 to 45 μm, and more preferably 12 μm to 35 μm.

[0029] In an optional embodiment, the thickness of the bulk film is 2 μm to 40 μm, preferably 3 μm to 39 μm, and more preferably 12 μm to 28 μm.

[0030] In an alternative embodiment, the bulk membrane comprises at least one of a polymer membrane and a ceramic membrane.

[0031] In an alternative embodiment, the polymer film includes at least one of a polyamide film, a polyimide film, a polyolefin film, a polyacrylonitrile film, a cellulose film, a polyester film, a nanofiber nonwoven film, and an aramid film.

[0032] In an optional embodiment, the thickness of the composite material layer is 0.3 μm to 9 μm, preferably 0.4 μm to 8 μm, and more preferably 1.2 μm to 5 μm.

[0033] In a second aspect, the present invention provides a method for preparing an isolation membrane as described in any of the aforementioned embodiments, comprising the following steps: coating a composite material layer slurry containing an inorganic binder and inorganic particles on at least one side of a main membrane, and drying.

[0034] In an optional embodiment, the composite material layer slurry has at least one of the following characteristics:

[0035] Feature 6: The solid content of the composite material layer slurry is 2% to 50%, preferably 6% to 48%, and more preferably 20% to 43%;

[0036] Feature 7: The viscosity of the composite material layer slurry is 10 cp to 1000 cp, preferably 20 cp to 350 cp, and more preferably 20 cp to 100 cp.

[0037] In an optional embodiment, the drying is performed at 50° C. to 70° C. for 2 min to 5 min.

[0038] In a third aspect, the present invention provides an electrochemical device, comprising the separator according to any one of the aforementioned embodiments.

[0039] In a fourth aspect, the present invention also provides an isolation membrane, which includes a main membrane and a composite material layer arranged on at least one side surface of the main membrane; the composite material layer contains crystals formed by an inorganic binder, and the crystals also include needle-like whiskers, flaky crystals and spherical crystals.

[0040] In a fifth aspect, the present invention also provides an isolation membrane, which includes a main membrane and a composite material layer arranged on at least one side surface of the main membrane; the composite material layer contains crystals formed by an inorganic binder, and the crystals include needle-like whiskers and flake crystals.

[0041] In a sixth aspect, the present invention further provides an isolation membrane, which includes a main membrane and a composite material layer arranged on at least one side surface of the main membrane; the composite material layer contains crystals formed by an inorganic binder, and the crystals include needle-like whiskers and spherical crystals.

[0042] In the seventh aspect, the present invention also provides an isolation membrane, which includes a main membrane and a composite material layer arranged on at least one side surface of the main membrane; the composite material layer contains crystals formed by an inorganic binder, and the crystals include at least one of lamellar crystals and spherical crystals and needle-shaped whiskers.

[0043] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the diameter of the needle-shaped whiskers is 40 nm to 900 nm, preferably 50 nm to 600 nm.

[0044] In an optional embodiment, in the isolation film provided by any one of the fourth to seventh aspects, some crystals together form a whisker group, and the remaining crystals are located between the inorganic particles.

[0045] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the longest length of the whisker group is 1 μm to 20 μm, preferably 5 μm to 11 μm.

[0046] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the whisker group is in a "grass-like" shape.

[0047] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the longest distance between any two points on the surface of the plate-like crystal is 1 μm to 3 μm.

[0048] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the longest distance between any two points on the surface of the spherical crystal is 1 μm to 3 μm.

[0049] In an optional embodiment, in the isolation membrane provided in any one of the fourth to seventh aspects, the composite material layer further contains inorganic particles with an average particle size of 10 nm to 5 μm, preferably contains inorganic particles with an average particle size of 11 nm to 4.9 μm.

[0050] In an optional embodiment, in the isolation film provided in any one of the fourth to seventh aspects, the thickness of the isolation film is 2.3 μm to 48 μm, preferably 3 to 45 μm, and more preferably 12 μm to 35 μm.

[0051] In an optional embodiment, in the isolation membrane provided in any one of the fourth to seventh aspects, the thickness of the composite material layer is 0.3 μm to 9 μm, preferably 0.4 μm to 8 μm, and more preferably 1.2 μm to 5 μm.

[0052] In an optional embodiment, in the isolation membrane provided in any one of the fourth to seventh aspects, the thickness of the main membrane is 2 μm to 40 μm, preferably 3 μm to 39 μm, and more preferably 12 μm to 28 μm.

[0053] The beneficial effects of the present invention include:

[0054] The present invention provides a composite material layer including an inorganic binder and inorganic particles on at least one side of the main body membrane, wherein the inorganic particles have relatively excellent wettability to organic electrolytes, especially to carbonate solvents with high dielectric constants that are difficult to be wetted by polyolefin membranes. In addition, the inorganic particles also have excellent heat resistance and non-flammable and refractory properties, which are conducive to making the isolation membrane have good heat resistance and mechanical properties. On this basis, combined with the use of an inorganic binder, it is conducive to ensuring that the isolation membrane can be used more stably and persistently under high temperature conditions, thereby enabling the electrochemical device containing the isolation membrane to operate safely and efficiently under high temperature conditions.

[0055] For example, the use of the above-mentioned inorganic binder can avoid the problems of inorganic particles falling off and falling off in the composite material layer that are easy to occur when using organic adhesives in the prior art. The main reasons for these problems are: organic adhesives have a significant swelling problem in the electrolyte. Once the electrolyte is absorbed, it is easy to cause the performance of the battery cell to decline. In addition, organic adhesives are unstable at high temperatures and are easy to melt or decompose, resulting in the failure of their bonding with inorganic ceramic particles.

[0056] Based on this, the present invention eliminates the traditional organic adhesive in the composite material layer and adopts an inorganic adhesive. The inorganic adhesive is not easy to swell in the electrolyte, has low cost, simple operation, good bonding effect and is environmentally friendly. In addition, the inorganic adhesive can overcome the defect of the organic adhesive's unstable performance at high temperature and show excellent high temperature resistance.

[0057] That is, the isolation membrane provided by the present invention has both excellent peel strength, puncture strength, wettability and air permeability, and good ionic conductivity, and can be used relatively stably and durably under high temperature conditions, thereby enabling the electrochemical device containing the isolation membrane to operate safely and efficiently under high temperature conditions.

[0058] The preparation method of the isolation membrane provided by the present invention is simple, easy to prepare on an industrial scale, and has a good industrial prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0060] Figure 1 This is a SEM image of the surface of a certain area in the isolation film (denoted as 2NSO5-22) prepared in Example 3;

[0061] Figure 2 for Figure 1 A magnified view of the SEM results at the first box (in order from top to bottom);

[0062] Figure 3 for Figure 1 The enlarged view of the SEM results in the second box (in order from top to bottom);

[0063] Figure 4 This is a SEM image of the surface of another area of ​​the isolation film (denoted as 2NSO5-22) prepared in Example 3;

[0064] Figure 5 This is a SEM image of the surface of a certain area in the isolation film (denoted as 2NSO5-30) prepared in Example 5;

[0065] Figure 6 for Figure 5 A magnified view of the SEM results in the box;

[0066] Figure 7 for Figure 6A magnified view of the SEM results in the box;

[0067] Figure 8 This is a SEM image of the surface of a certain area in the isolation film (denoted as 2NSO10-22) prepared in Example 6;

[0068] Fig. 9 This is a SEM image of the surface of a certain area in the isolation film (denoted as 2NSO20-22) prepared in Example 7;

[0069] Fig.10 This is a SEM image of the surface of another area of ​​the isolation membrane prepared in Example 7;

[0070] Fig.11 This is a SEM image of the surface of a certain area in the isolation film (denoted as NSO5-22) prepared in Example 11;

[0071] Fig.12 for Fig.11 A magnified view of the SEM results in the box;

[0072] Fig.13 This is a SEM image of the surface of another area of ​​the isolation film prepared in Example 11;

[0073] Fig.14 for Fig.13 A magnified view of the SEM results in the box;

[0074] Fig.15 This is a SEM image of a cross section of the isolation membrane prepared in Example 4 after being kept at 130° C. for 1 hour;

[0075] Fig.16 This is a SEM image of a cross section of the isolation membrane prepared in Example 3 after being kept at 200° C. for 1 hour. DETAILED DESCRIPTION

[0076] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0077] The isolation film provided by the present invention and its preparation method and application are described in detail below.

[0078] The invention provides an isolation film, which comprises a main body film and a composite material layer coated on at least one side surface of the main body film; the composite material layer comprises an inorganic binder and inorganic particles.

[0079] The above-mentioned “at least one side” can be understood as: the composite material layer can be arranged on the surface of any one side of the main film, or the composite material layer can be arranged on the surfaces of both sides of the main film.

[0080] The inorganic particles in the composite material layer have a high specific surface area (e.g. 10m 2 / g~88m 2 / g) and good hydrophilicity, and has relatively excellent wettability to organic electrolytes, especially to carbonate solvents with high dielectric constants and difficult to be wetted by polyolefin membranes. In addition, the inorganic particles also have excellent heat resistance and non-flammable and refractory properties, which are conducive to making the isolation membrane have good heat resistance and mechanical properties. The inorganic binder used in the composite material layer of the present invention can not only overcome the defect of unstable performance of organic adhesives at high temperatures and show excellent high temperature resistance, but also has the characteristics of not being easy to swell in electrolytes, low cost, simple operation, good bonding effect and environmental friendliness.

[0081] In the present invention, the inorganic binder includes a component with a chemical formula of M2O·nSiO2 and / or a component with a chemical formula of a(Al2O3·mH2O)·bH x ·cH2O aluminum sol, wherein M includes at least one of Na, K and Li, 1≤n≤4; Al2O3·mH2O is hydrated aluminum oxide, H x It is a peptizing agent, and b is smaller than a, c and m.

[0082] In some optional embodiments, the inorganic binder includes a component with a chemical formula of M2O·nSiO2, but does not contain a component with a chemical formula of a(Al2O3·mH2O)·bH x · Aluminum sol in cH2O.

[0083] In some optional embodiments, the inorganic binder comprises a (Al2O3·mH2O)·bH x ·cH2O, but does not contain a component with the chemical formula M2O·nSiO2.

[0084] In some optional embodiments, the inorganic binder may include a component with a chemical formula of M2O·nSiO2 and a component with a chemical formula of a(Al2O3·mH2O)·bH x · Aluminum sol in cH2O.

[0085] The component of the chemical formula M2O·nSiO2 is an inorganic compound composed of metal cations and polymer silicate anions.

[0086] In the present invention, the cation in M2O·nSiO2 is selected from at least one of Na, Li and K, which are light in weight and small in ionic radius, which is not only conducive to improving the energy density and ion mobility of the material, but also avoids the harm of using magnetic elements such as Fe, Cr or Ni or other heavy metal elements to the battery or the environment. In some typical embodiments, M is at least one of Na and Li.

[0087] In the present invention, n in M2O·nSiO2 represents the number of SiO2 units in the polymer anion, which is called the modulus, n=SiO2 / M2O (molar ratio). Exemplarily, the value of n can be 1, 1.5, 2, 2.5, 3, 3.5 or 4.

[0088] The outer electron configuration of the silicon atom of the inorganic binder used in the present invention is 3s 2 3p 2 , which has the property of heating dehydration polymerization. As the temperature of the liquid inorganic binder rises, the water in the inorganic binder evaporates, the silicate anions aggregate into a film, and more silanol groups are produced. The adjacent silanol groups condense to form Si-O-Si bonds, and the remaining water molecules continue to catalyze the dehydration condensation of the silanol groups. The viscosity of the adhesive continues to increase, and finally a three-dimensional network structure connected by Si-O-Si bonds is formed. This structure has strong bonding properties.

[0089] The value of the modulus n in the inorganic binder will affect the bonding performance of the inorganic binder. The larger the modulus, the stronger the bonding force, and the easier it is to harden into a film. The heat resistance of the isolation membrane and the peel strength of the composite material layer will also increase with the increase of the modulus n. However, if the value of the modulus n is too large, it will not only increase the viscosity of the inorganic binder and deteriorate the operability, but also reduce the proportion of cations, resulting in a decrease in ionic conductivity. Based on this, the present invention specifically uses an inorganic binder with n of 1 to 4.

[0090] In the present invention, the aluminum sol is essentially a colloidal solution in which charged aluminum oxide particles are uniformly dispersed in water, wherein the shape of the aluminum oxide particles includes at least one of feather-like, flocculent and fibrous.

[0091] In some optional embodiments, the particle size range of aluminum sol can be 5nm to 200nm, such as 5nm, 10nm, 20nm, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm or 200nm, etc., or other values ​​within the range of 5nm to 200nm.

[0092] In some optional embodiments, the pH value of the aluminum sol may be 4 to 10, such as 4, 5, 6, 7, 8, 9 or 10, or other values ​​within the range of 4 to 10.

[0093] In the present invention, the composite material layer contains crystals formed by an inorganic binder; some of the crystals together form a whisker group, the crystals at least include needle-shaped whiskers, and the remaining crystals are located between the inorganic particles.

[0094] In some optional embodiments, the crystals further include at least one of plate-like crystals and spherical crystals.

[0095] Specifically, in some embodiments, the crystal has only needle-shaped whiskers; in some embodiments, the crystal has both needle-shaped whiskers and flake-shaped crystals; in some embodiments, the crystal has both needle-shaped whiskers and spherical crystals; in some embodiments, the crystal has both needle-shaped whiskers, flake-shaped crystals and spherical crystals.

[0096] The diameter of the whisker is 40nm to 900nm. In some preferred embodiments, the diameter of the whisker can be 50nm to 600nm, such as 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm or 600nm, etc., or any value or any range within the range of 50nm to 600nm.

[0097] The longest length of the whisker group is 1 μm to 20 μm. In some preferred embodiments, the longest length of the whisker group can be 5 μm to 11 μm, such as 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm or 11 μm, etc., or any value or any range within the range of 5 μm to 11 μm.

[0098] In this article, the diameter of the whisker and the longest length of the whisker group can be measured by scanning electron microscopy. Among them, the whisker is a special crystal form, which is a fibrous crystal grown from high-purity raw materials. The diameter of the whisker can be understood as the width value relative to the whisker length. The diameter of crystals of other shapes can be understood as the maximum value obtained by comparing the shortest distance between any two points on the surface of the crystal.

[0099] In some alternative embodiments, the whisker population may be in a "brush-like" configuration.

[0100] In some optional embodiments, the longest distance between any two points on the surface of the plate-like crystal is 1 μm to 3 μm.

[0101] In some optional embodiments, the longest distance between any two points on the surface of the spherical crystal is 1 μm to 3 μm.

[0102] As far as the scheme of the present invention is concerned, during the drying and dehydration process of the isolation membrane, the inorganic binder in the composite material layer will crystallize. The crystallization stage is the hardening process of the inorganic binder. At this time, the gel body is transformed into crystals. Crystals in some areas gradually grow, intersperse between the composite material layers, overlap each other, and cross-climb to transform the gel into a three-dimensional space firmly combined and dense "grass-like" whisker group; the other part is located (for example, evenly dispersed) between the inorganic particles, interlaced with each other to form a network support. The whiskers in the composite material layer are tightly combined with the inorganic particles to form a "reinforced concrete" structure.

[0103] The heat resistance of the isolation membrane in the present invention is related to the whiskers grown in the composite material layer. The "grass-like" whisker group is "rooted" in the composite material layer and "pins" the moving shrinkage interface at high temperatures, playing a "pinning effect" in the isolation membrane, which can effectively inhibit the shrinkage of the isolation membrane; in addition, the dispersed high-temperature resistant inorganic whiskers form a network, so that the composite material layer as a whole has the characteristics of continuous self-support, so that the composite material layer can still maintain good integrity at high temperatures and when the main film is melted, without breaking or pulverizing, showing an excellent geothermal protection effect.

[0104] In some optional embodiments, the mass of the inorganic binder is 1% to 35% of the mass of the inorganic particles in the composite material layer, such as 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32% or 35%, etc., and can also be other values ​​within the range of 1% to 35%, preferably 1 to 20%, and more preferably 1 to 12%.

[0105] In some optional embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the composite material layer, such as 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32% or 35%, etc., and can also be other values ​​within the range of 1% to 35%. In some preferred embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 20% of the mass of the inorganic particles in the composite material layer; in some more preferred embodiments, the mass of the component with the chemical formula M2O·nSiO2 is 1% to 12% of the mass of the inorganic particles in the composite material layer.

[0106] The more the content of the component with the chemical formula M2O·nSiO2 in the composite material layer, the larger the whiskers contained in the composite material layer. In addition, the modulus of the component with the chemical formula M2O·nSiO2 will also affect the size of the whiskers. The higher the modulus, the larger the diameter of the "grass-like" whisker group and the dispersed whiskers, and the better the heat resistance of the corresponding isolation film. In addition, the component with the chemical formula M2O·nSiO2 in the above content range can avoid the problem of low bonding strength caused by too little addition on the one hand, and can avoid too much addition causing rapid agglomeration of slurry particles on the other hand, thereby causing phenomena such as film surface leakage, uneven thickness of the composite material layer, shrinkage film curling, etc.

[0107] By combining an inorganic binder having the above characteristics with inorganic particles, the inorganic particles can be used as a curing agent for the inorganic binder. The inorganic particles and the inorganic binder can form a network structure through hydrogen bonds, van der Waals forces and their own bonding to achieve good bonding. Even under high temperature conditions, they will not melt or decompose, and can maintain their own size and structure well, which is beneficial to improving the performance of the battery.

[0108] In some optional embodiments, when the component with the chemical formula M2O·nSiO2 accounts for 5% of the mass of the inorganic particles in the composite material layer, the diameter of the whiskers is 50nm to 415nm, such as 50nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm or 415nm, etc., or it can be any value or any range within the range of 50nm to 415nm.

[0109] In some optional embodiments, when the component with the chemical formula M2O·nSiO2 accounts for 20% of the mass of the inorganic particles in the composite material layer, the diameter of the whiskers is 300nm to 600nm, such as 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm, 520nm, 540nm, 560nm, 580nm or 600nm, etc., or it can be any value or any range within the range of 300nm to 600nm.

[0110] In some optional embodiments, the inorganic particles may include, by way of example but not limitation, at least one of kaolin, boehmite, clay, molecular sieves (such as ZSM-5, etc.), Al2O3 (including α-type, β-type and / or γ-type, etc.), SiO2, BaSO4, BaO, MgO, CuO, LiAlO2, ZrO2, Fe2O3, BaTiO3, α-V2O5, PbTiO3, CaSiO3, titanium dioxide (including TiO2, rutile and / or anatase, etc.), LiF, MgF2, BaF2, TiB2, Mg(OH)2, MoS2, SiC, Si3N4 and carbon nanotubes (CNTs). In some preferred embodiments, the inorganic particles may include at least one of boehmite, Al2O3, SiO2 and BaTiO3.

[0111] In some optional embodiments, the average particle size of the inorganic particles can be 10nm to 5μm, such as 10nm, 20nm, 50nm, 80nm, 100nm, 200nm, 500nm, 800nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm, etc., or any value or any range within the range of 10nm to 5μm. In some preferred embodiments, the average particle size of the inorganic particles is 11nm to 4.9μm.

[0112] In some optional embodiments, the bulk film includes at least one of a polymer film and a ceramic film. Wherein, the polymer film may exemplarily but not limitatively include at least one of a polyamide film, a polyimide film, a polyolefin film, a polyacrylonitrile film, a cellulose film, a polyester film and an aramid film. Wherein, polyolefins may exemplarily include polyethylene, polypropylene, polyvinylidene fluoride and polytetrafluoroethylene, etc., and polyesters may exemplarily include polyethylene terephthalate, etc. In addition, other bulk films may also be used according to actual needs.

[0113] In some optional embodiments, the bulk film may be in a single-layer form, a double-layer form, or a multi-layer form (the number of layers is greater than 2). When the number of layers of the bulk film is ≥ 2, the thickness of each layer of the bulk film may be equal or unequal, and the material of each layer of the bulk film may be the same or different. When the number of layers of the bulk film is ≥ 2, the layers may be combined together by lamination and / or coextrusion.

[0114] In some optional embodiments, the thickness of the bulk film can be 2 μm to 40 μm, such as 2 μm, 2.5 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm or 40 μm, etc., or any value or any range within the range of 2 μm to 40 μm. In some preferred embodiments, the thickness of the bulk film is 3 μm to 39 μm; in some more preferred embodiments, the thickness of the bulk film is 12 μm to 28 μm.

[0115] In some optional embodiments, the thickness of the composite material layer can be 0.3 μm to 9 μm, such as 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm or 9 μm, etc., or any value or any range within the range of 0.3 μm to 9 μm. In some preferred embodiments, the thickness of the composite material layer is 0.4 μm to 8 μm; in some more preferred embodiments, the thickness of the composite material layer is 1.2 μm to 5 μm.

[0116] If the thickness of the composite material layer is higher than 9μm, it will easily lead to increased difficulty in coating, and at the same time, the electrolyte retention rate and the mass of the isolation membrane will increase, resulting in a decrease in the energy density of the battery; if the thickness of the composite material layer is lower than 0.3μm, it will easily lead to a decrease in the thermal dimensional stability, liquid retention rate and capacity retention rate of the isolation membrane.

[0117] With the increase of M2O·nSiO2 content and the thickness of the composite material layer, the heat resistance of the separator is better and the peel strength of the composite material layer is higher. The reason is that: on the one hand, the increase in thickness is equivalent to the increase in the content of inorganic binder and inorganic particles per unit area, which is conducive to improving the bonding strength between inorganic particles and the main film, inhibiting the shrinkage of the separator at high temperature, and improving the heat resistance of the separator; on the other hand, with the increase of M2O·nSiO2 content, the interaction between the inorganic binder and the inorganic particles will also intensify, and the inorganic binder and the inorganic particles will be more closely combined. In addition, with the increase of M2O·nSiO2 content and thickness in the composite material layer, the ionic conductivity of the separator increases, which may be because the main film is difficult to be wetted, resulting in poor electrolyte retention and absorption rate, while the porous structure in the composite material layer and the good lyophilicity of inorganic particles can increase the wettability of the separator. The good wettability of the separator can not only effectively shorten the electrolyte filling time during the battery assembly process, but also improve the electrolyte retention capacity, which is more conducive to the effective transmission of ions during the battery operation. The thicker the composite material layer, the more electrolyte liquid retention and liquid absorption, and the more inorganic binder content will increase the conductive ion content, all of which will increase the ionic conductivity of the separator, but too high a composite material layer thickness will increase the ion transmission distance and thus reduce the ionic conductivity. In addition, when the inorganic binder content is too high, not only will the slurry be difficult to coat, but it will also cause the composite material layer slurry to agglomerate quickly, the particle size will increase significantly, the slurry stability will deteriorate, and the composite material layer will leak.

[0118] In some optional embodiments, the total thickness of the isolation film can be 2.3μm to 48μm, such as 2.3μm, 2.5μm, 3μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm or 48μm, etc., or any value or any range within the range of 2.3μm to 48μm. In some preferred embodiments, the total thickness of the isolation film is 3μm to 45μm; in some more preferred embodiments, the total thickness of the isolation film is 12μm to 35μm.

[0119] As mentioned above, the isolation membrane provided by the present invention has both excellent peel strength, puncture strength, wettability and air permeability, and good ionic conductivity, and can be used relatively stably and durably under high temperature conditions, thereby enabling the electrochemical device containing the isolation membrane to operate safely and efficiently under high temperature conditions.

[0120] Correspondingly, the present invention also provides a method for preparing the above-mentioned isolation membrane, comprising the following steps: coating a composite material layer slurry containing an inorganic binder and inorganic particles on at least one side of the body membrane, and drying.

[0121] The coating may be exemplarily but not limitatively carried out by coating method (such as extrusion transfer coating method or dip coating method, etc.), blade coating method, electrostatic spraying method, gravure or micro gravure coating method, as long as the composite material layer slurry can be coated on the surface of the main film.

[0122] In some optional embodiments, the solid content of the composite material layer slurry can be 2% to 50%, such as 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., or any value or any range within the range of 2% to 50%. In some preferred embodiments, the solid content of the composite material layer slurry is 6% to 48%; in some more preferred embodiments, the solid content of the composite material layer slurry is 20% to 43%.

[0123] In some optional embodiments, the viscosity of the composite material layer slurry can be 10cp to 1000cp, such as 10cp, 20cp, 50cp, 80cp, 100cp, 200cp, 500cp, 800cp or 1000cp, etc., or any value or any range within the range of 10cp to 1000cp. In some preferred embodiments, the viscosity of the composite material layer slurry is 20cp to 350cp; in some more preferred embodiments, the viscosity of the composite material layer slurry is 20cp to 100cp.

[0124] The composite material layer slurry is obtained by mixing the raw materials for preparing the composite material layer with a solvent, and the solvent may be water, for example.

[0125] The raw materials for preparing the composite material layer include an inorganic binder and inorganic particles, and further, may include an auxiliary agent, such as at least one of a dispersant, a wetting agent, a thickener and a flame retardant.

[0126] The dispersant may include, for example, at least one of polyacrylamide, sodium hexametaphosphate, and methylpentanol.

[0127] The wetting agent may include, for example, at least one of ethanol, propylene glycol, glycerin, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, fatty acid ester sulfate, vinyl triethoxysilane, and the like.

[0128] The thickener may include, for example, carboxymethyl cellulose (CMC) and the like.

[0129] The flame retardant may include, for example, at least one of brominated flame retardants, ammonium phosphate, ammonium hydroxide, alumina trihydrate, phosphate ester, and the like.

[0130] The mass of the dispersant can be 0.2-5% of the mass of the inorganic particles, such as 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be any value or any range within the range of 0.2-5%.

[0131] The mass of the wetting agent can be 0.05-5% of the mass of the inorganic particles, such as 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be any value or any range within the range of 0.05-5%.

[0132] The mass of the thickener can be 0.5-5% of the mass of the inorganic particles, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be any value or any range within the range of 0.5-5%.

[0133] The mass of the flame retardant can be 1-5% of the mass of the inorganic particles, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., or it can be any value or any range within the range of 1-5%.

[0134] In some optional embodiments, the drying temperature can be carried out at 50°C to 70°C (such as 50°C, 55°C, 60°C, 65°C or 70°C, etc.) for 2min to 5min (such as 2min, 2.5min, 3min, 3.5min, 4min, 4.5min or 5min, etc.).

[0135] Drying conditions will affect the crystals. At the beginning of drying, the water in the adhesive evaporates, anions gather into a film, and more silanol groups are produced. The water molecules in the adhesive rearrange, catalyzing the condensation between adjacent silanol groups to form Si-O-Si bonds. As the temperature rises or the drying time increases, the remaining water molecules continue to catalyze the dehydration condensation of the silanol groups, and then a local reaction occurs on the surface of the dispersed anhydrous compound particles to form a gel, with a significant exothermic effect. The crystallization stage is the hardening process of the inorganic binder. At this time, the gel is transformed into crystals. The crystals gradually grow and overlap and cross-climb each other to transform the gel into a three-dimensional space that is firmly bonded and dense, accompanied by a small amount of heat release.

[0136] If the drying temperature is too high, the whiskers may not grow tightly enough and the crystal structure may become loose, which will weaken their mechanical properties. If the drying temperature is set too low, it will not only cause the crystal growth rate to slow down, but also require an extended drying cycle to ensure that the isolation film reaches the established moisture standard, reducing production efficiency. In addition, high-temperature drying will also increase the energy consumption of the drying equipment, which will have an adverse impact on cost control.

[0137] If the drying time is too long, the whisker size will increase abnormally, and the energy consumption will also increase, which is not conducive to cost control and also hinders the improvement of production efficiency. If the drying time is too short, it is difficult to ensure that the moisture content of the isolation film meets the production standards.

[0138] In addition, the present invention also provides an electrochemical device (such as a lithium-ion battery), which includes the above-mentioned isolation membrane.

[0139] Specifically, the electrochemical device comprises a positive electrode, a negative electrode and a separator, wherein the separator is used to separate the positive electrode from the negative electrode. The electrochemical device having the separator has good safety in use.

[0140] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0141] Example 1

[0142] This embodiment provides an isolation membrane with a total thickness of 13 μm, which includes a porous polyethylene (PE) main membrane with a thickness of 9 μm and a composite material layer coated on both sides of the main membrane (the thickness of the composite material layer on each side is 2 μm).

[0143] The composite material layer slurry used for preparing the composite material layer is obtained by dissolving the preparation raw materials in water. The composite material layer slurry has a solid content of 26.3% and a viscosity of about 20 cp.

[0144] In terms of mass, the raw materials include 100 parts of inorganic particles (alumina powder with an average particle size of 500 nm), 5 parts of inorganic binder (Na2O·3SiO2), 1.5 parts of thickener (CMC), 0.5 parts of dispersant (polyacrylamide) and 0.1 parts of wetting agent (vinyl triethoxysilane).

[0145] The preparation method of the isolation film comprises:

[0146] Step 1: Add inorganic particles, dispersant and thickener into 300 parts of deionized water according to the amount of the above-mentioned raw materials, stir at a speed of 2000 rpm for 4 hours to obtain a first slurry; ball mill the first slurry in a ball mill at a ball milling rate of 60 rpm for 24 hours to obtain a second slurry.

[0147] Step 2: Filter the second slurry, add an inorganic binder and a wetting agent to the filtered second slurry, and stir at a rotation speed of 500 rpm for 1 hour to obtain a composite material layer slurry.

[0148] Step 3: The composite material layer slurry is evenly coated on both sides of the main film on a coating machine, and vacuum dried at 60° C. for 5 minutes to obtain an isolation film with composite material layers on both sides of the main film.

[0149] Example 2

[0150] The difference between this embodiment and embodiment 1 is that the amount of the inorganic binder used is 2 parts, and the inorganic binder is Na2O·2SiO2.

[0151] Example 3

[0152] The difference between this embodiment and embodiment 2 is that the amount of the inorganic binder used is 5 parts.

[0153] Example 4

[0154] The difference between this embodiment and embodiment 3 is that a composite material layer with a thickness of 2 μm is provided only on one surface of the main film.

[0155] Example 5

[0156] The difference between this embodiment and embodiment 4 is that the thickness of the composite material layer is 3 μm.

[0157] Example 6

[0158] The difference between this embodiment and embodiment 2 is that the amount of the inorganic binder used is 10 parts.

[0159] Example 7

[0160] The difference between this embodiment and embodiment 2 is that the amount of the inorganic binder used is 20 parts.

[0161] Example 8

[0162] The difference between this embodiment and embodiment 3 is that the inorganic binder is Na2O·1.5SiO2.

[0163] Example 9

[0164] The difference between this embodiment and embodiment 8 is that a composite material layer with a thickness of 2 μm is provided only on one surface of the main film.

[0165] Example 10

[0166] The difference between this embodiment and embodiment 9 is that a composite material layer with a thickness of 3 μm is provided only on one surface of the main film.

[0167] Embodiment 11

[0168] The difference between this embodiment and embodiment 3 is that the inorganic binder is Na2O·SiO2.

[0169] Example 12

[0170] The difference between this embodiment and embodiment 11 is that the amount of inorganic binder used is 10 parts.

[0171] Embodiment 13

[0172] The difference between this embodiment and embodiment 1 is that the inorganic binder is Na2O·4SiO2.

[0173] Embodiment 14

[0174] The difference between this embodiment and embodiment 1 is that the inorganic binder is K2O·3SiO2.

[0175] Embodiment 15

[0176] The difference between this embodiment and embodiment 1 is that the inorganic binder is Li2O·3SiO2.

[0177] Example 16

[0178] The difference between this embodiment and embodiment 1 is that the thickness of the main film is 2 μm, and the thickness of the composite material layer on each side surface of the main film is 0.3 μm.

[0179] The solid content of the composite material layer slurry is 2%, and the viscosity of the composite material layer slurry is 10 cp.

[0180] The inorganic particles are SiO2; the mass of Na2O·3SiO2 is 1% of the mass of the inorganic particles in the composite material layer; the mass of the thickener is 0.5% of the mass of the inorganic particles; the mass of the dispersant is 0.2% of the mass of the inorganic particles; the mass of the flame retardant (ammonium phosphate) is 1% of the mass of the inorganic particles; and the mass of the wetting agent is 0.1% of the mass of the inorganic particles.

[0181] The drying temperature is 50°C and the drying time is 5 minutes.

[0182] Embodiment 17

[0183] The difference between this embodiment and embodiment 1 is that the thickness of the main film is 40 μm, and the thickness of the composite material layer on each side surface of the main film is 9 μm.

[0184] The solid content of the composite material layer slurry is 50%, and the viscosity of the composite material layer slurry is 1000 cp.

[0185] The inorganic particles are BaTiO3; the mass of Na2O·3SiO2 is 35% of the mass of the inorganic particles in the composite material layer; the mass of the thickener is 5% of the mass of the inorganic particles; the mass of the dispersant is 5% of the mass of the inorganic particles; the mass of the flame retardant (alumina trihydrate) is 5% of the mass of the inorganic particles; and the mass of the wetting agent is 5% of the mass of the inorganic particles.

[0186] The drying temperature is 70°C and the drying time is 2 minutes.

[0187] Embodiment 18

[0188] The difference between this embodiment and embodiment 1 is that the mass of Na2O·3SiO2 is 12% of the mass of the inorganic particles in the composite material layer. The inorganic particles are boehmite.

[0189] Embodiment 19

[0190] The difference between this comparative example and Example 1 is that the inorganic binder is Na2O·5SiO2.

[0191] Embodiment 20

[0192] The difference between this comparative example and Example 1 is that the mass of the inorganic binder is 40% of the mass of the inorganic particles in the composite material layer.

[0193] Embodiment 21

[0194] The difference between this comparative example and Example 1 is that the thickness of the composite material layer is 12 μm.

[0195] Embodiment 22

[0196] The difference between this embodiment and embodiment 1 is that the inorganic binder is aluminum sol.

[0197] Comparative Example 1

[0198] The difference between this comparative example and Example 1 is that no composite material layer is provided on the surface of the main membrane.

[0199] Comparative Example 2

[0200] The difference between this comparative example and Example 1 is that the inorganic binder is replaced by a polymethacrylic acid adhesive.

[0201] Comparative Example 3

[0202] The difference between this comparative example and Example 1 is that the inorganic binder is replaced by polyacrylamide adhesive.

[0203] Test example

[0204] (1) The isolation membranes obtained in Examples 1 to 21 and Comparative Examples 1 to 3 were subjected to performance testing. The performance results are shown in Tables 1 and 2.

[0205] Performance test method reference:

[0206] ① Shrinkage rate: Cut the isolation film into multiple 120mm×100mm (length×width) sizes in the longitudinal (MD) and transverse (TD) directions, cover the surface of the isolation film with a piece of A4 paper, put it in an oven at 130℃, 150℃, and 200℃ for 1 hour, measure the size of the direction after heat shrinkage, and calculate the shrinkage ratio. The shrinkage rate values ​​of the isolation film in Table 1 are based on the average values ​​of each direction after three measurements in the MD and TD directions.

[0207] ②. Peel strength: Test the peel strength between the composite material layer and the main body film on a universal tensile tester. Use a sampler to cut the composite material layer isolation film into a sample strip of 150mm×30mm (length×width), adhere it to the double-sided tape of the test plate, and then adhere a 200mm×20mm (length×width) transparent tape on top of the sample strip, and then use a cylindrical roller to naturally press the isolation film in the same direction. When the isolation film is a single-sided coated composite material layer, its corresponding main body film faces down and the composite material layer faces up. Peel off one end of the transparent tape from the isolation film composite material layer until the adhesion length between the transparent tape and the isolation film composite material layer is 80mm, fold the free end of the transparent tape in half, clamp the free end of the transparent tape and the test plate on the upper and lower clamps respectively, and use a tensile tester in the same environment to continuously peel at a tensile speed of 100mm / min until the composite material layer and the main body film are completely separated, and directly read and record the peel strength of the isolation film composite material layer.

[0208] ③. Air permeability and puncture strength: refer to GBT36363-2018 standard; thickness is measured by Marr film thickness gauge.

[0209] ④. Water contact angle: Use contact angle measuring instrument according to GBT30693-2014 standard.

[0210] ⑤. Wettability of electrolyte: The wettability of the separator is characterized by dripping electrolyte droplets on the separator surface and measuring the size change of the droplets formed at 5s and 5min. Specifically, the droplet size is expressed by measuring the sum of the longest distances in the MD and TD directions divided by 2, and the droplet size corresponding to 5s and 5min is measured and the difference is divided by 2 to express the wettability.

[0211] ⑥. Ionic conductivity: Cut 5 isolation membranes that match the resistance test mold, put the isolation membranes into a 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte, the solvent of which is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1, and keep the seal and soak for 2 hours. Use an electrochemical workstation at 25°C, 0.01Hz~1×10 6The electrochemical impedance spectrum is tested and recorded in the frequency range of Hz, with the number of isolation membrane layers as the horizontal axis and the isolation membrane resistance as the vertical axis. The slope and linear fit of the curve are calculated. When the linear fit is greater than 0.99, the slope (k) is the isolation membrane impedance value. The formula The ionic conductivity of the isolation membrane is calculated, where σ is the ionic conductivity of the isolation membrane, d is the thickness of the isolation membrane, k is the impedance value of the isolation membrane, and S is the area used during the isolation membrane test.

[0212] ⑦. Slurry particle size: The prepared composite material layer slurry is tested for particle size using Malvern laser particle size analyzer MS3000.

[0213] ⑧. Slurry stability time: Particle size D measured by Malvern laser particle size analyzer MS3000 50 Greater than 2μm time.

[0214] Table 1 Performance test results

[0215]

[0216] Table 2 Performance test results (continued)

[0217]

[0218] As can be seen from Table 1 and Table 2, the embodiments of the present invention use inorganic binders to replace traditional organic adhesives, and at the same time control the amount of inorganic binders and the modulus of inorganic binders, so that the prepared isolation membrane has high ionic conductivity, good wettability and good high temperature resistance. In some preferred methods, under the conditions that the thickness of the composite material layer is 4μm and the thickness of the isolation membrane does not exceed 13μm, the shrinkage rate of heat treatment at 200℃ for 1h can be less than 3% and no powder will fall off, indicating that the adhesive has not failed at this time, and the safety of the isolation membrane has been significantly improved, meeting the use requirements.

[0219] Comparing Examples 2 to 7 and Examples 9 to 10, it can be seen that as the amount of inorganic binder used and the thickness of the composite material layer increase, the heat resistance of the isolation film is better and the peel strength of the composite material layer is higher. This is because the increase in the amount of inorganic binder used intensifies the interaction between the inorganic binder and the inorganic particles, and the inorganic binder and the inorganic particles are more tightly combined; the increase in the thickness of the composite material layer is equivalent to increasing the content of inorganic binder and inorganic particles per unit area, thereby increasing the bonding strength between the inorganic particles and the main film, inhibiting the shrinkage of the isolation film at high temperatures, and improving the heat resistance.

[0220] In addition, compared with Comparative Example 1, the ionic conductivity of the isolation membrane provided in the above embodiment is significantly increased and increases with the increase in the amount of inorganic binder and the thickness of the composite material layer. This can be attributed to the fact that the bulk membrane (PE) is difficult to wet, resulting in poor electrolyte retention and liquid absorption, while the highly developed porous structure of the inorganic composite material layer and the good lyophilic properties of the inorganic particles significantly increase the wettability of the isolation membrane (the contact angle drops from 114° to below 14°). The good wettability of the isolation membrane can not only effectively shorten the filling time of the electrolyte during the battery assembly process, but also improve the retention capacity of the electrolyte, which is more conducive to the effective transmission of ions during the operation of the battery. Moreover, the thicker the composite material layer, the more electrolyte retention and liquid absorption, and the more inorganic binder content will increase the content of conductive ions, all of which will increase the ionic conductivity of the isolation membrane, but the excessively high thickness of the composite material layer will increase the ion transmission distance and thus reduce the ionic conductivity. In addition, when the content of inorganic binder is too high, not only will the composite material layer slurry be difficult to coat, but it will also cause the composite material layer slurry to agglomerate rapidly, significantly increase the particle size, and deteriorate the stability of the composite material layer slurry, leading to composite material layer leakage and other phenomena.

[0221] From the comparison of Example 3, Example 8, Example 11 and Example 12, it can be seen that with the same thickness and inorganic binder content, the heat resistance of the isolation membrane and the peel strength of the composite material layer will increase with the increase of the modulus of the inorganic binder, but the increase in the modulus will reduce the proportion of cations, resulting in a slight decrease in ionic conductivity. In addition, Example 3 containing 5 parts of Na2O·2SiO2 has a lower shrinkage rate than Example 12 containing 10 parts of Na2O·SiO2 at the same temperature, indicating that the modulus of the inorganic binder has a greater impact on the heat resistance of the isolation membrane.

[0222] It can be seen from Examples 1 and 19 to 21 that a too high modulus (such as Example 19) will reduce heat resistance, ionic conductivity and slurry stability. The more adhesive content, the larger the slurry particle size, the shorter the stabilization time, and it will cause leakage after exceeding a certain amount (such as Example 20), resulting in a sharp deterioration in performance. Although increasing the thickness will improve heat resistance, it will also increase the permeability and reduce the ionic conductivity, and will also reduce the volume energy density of the battery (such as Example 21).

[0223] This shows that the modulus, dosage of the inorganic binder and the thickness of the composite material layer will affect the performance of the isolation membrane. If the conditions are not set properly, the performance of the isolation membrane will be reduced.

[0224] Compared with Comparative Examples 2 and 3, all the isolation membranes obtained from the examples using inorganic binders with the same amount of organic adhesive and the same thickness of the composite material layer as those in the two comparative examples have higher heat resistance, peel strength and ionic conductivity.

[0225] (2) The isolation membranes obtained in various embodiments of the present invention were observed by scanning electron microscopy. The results showed that the composite material layers of the isolation membranes prepared in the embodiments of the present invention all contained crystals, some of which formed a group of "grass-like" whiskers, and the remaining crystals were located between the inorganic particles. The shapes of the crystals include needle-shaped, flake-shaped, and spherical; the diameters of the whiskers were all in the range of 40nm to 900nm, and the longest length of the whisker group was in the range of 1μm to 20μm. The longest distance between any two points on the surface of the flake crystals and the longest distance between any two points on the surface of the spherical crystals were 1μm to 3μm.

[0226] Among them, the scanning electron microscope images of the isolation films prepared in Example 3, Examples 5 to 7 and Example 11 are taken as examples. Figures 1 to 14 .

[0227] Depend on Figures 1 to 14 It can be seen that the composite material layer of the isolation membrane contains crystals, and the shapes of the crystals include needles, flakes and spheres.

[0228] Depend on Figures 1 to 7 It can be seen that in some areas of the composite material layer, the crystals are interspersed between the composite material layers and overlap and cross-climb each other, forming a "grass-like" whisker group that is firmly combined and dense in three-dimensional space; in some areas, the crystals are evenly dispersed between the inorganic particles, interlaced with each other to form a network support, and the whiskers between the composite material layers are tightly combined with the inorganic particles to form a "reinforced concrete" structure.

[0229] Moreover, with the increase of the amount of inorganic binder, the whiskers formed in the composite material layer become larger. At the amount of inorganic binder corresponding to Example 3 (5 parts), the diameter of the whiskers formed in the composite material layer is about 78nm~415nm; at the amount of inorganic binder corresponding to Example 7 (20 parts), the diameter of the whiskers formed in the composite material layer is about 300nm~586nm, and the morphology is also changed compared with Example 3. The whiskers in Example 7 are flake or spherical, and the main size of the whisker group (that is, the longest length of the whisker) is mostly in the range of 5μm~11μm.

[0230] It can be seen from the SEM images corresponding to Example 3 and Example 11 that the modulus of the inorganic binder will affect the size of the whiskers. The higher the modulus, the larger the "grass-like" whisker group and the whisker diameter, and the better the heat resistance of the corresponding isolation membrane, which further illustrates the influence of the size of the whiskers on the heat resistance of the isolation membrane.

[0231] It should be noted that when the ceramic isolation membrane is heated, the friction and adhesion between the ceramic layer and the main membrane layer, the gravity of the ceramic layer or the pressure applied during battery assembly will hinder the contraction and movement of the main membrane, making its structure intact and increasing its stability.

[0232] Fig.15 The SEM cross-sectional view of the separator of Example 4 after being kept at 130°C for 1 hour shows that the pores of the main membrane and the structure of the ceramic particle layer can be kept intact at this temperature. At higher temperatures, the main membrane will melt and the pores will close, but the ceramic particles will be embedded in the main membrane to form an interlocking structure to make the separator structure intact, avoid direct contact between the positive and negative electrodes, and inhibit further temperature increases, thereby improving the thermal safety of the separator.

[0233] Fig.16 The SEM cross-sectional view of the isolation membrane of Example 3 after being kept at 200°C for 1 hour shows that the molten bulk membrane is embedded in the gaps between the alumina particles to form an interlocking interface structure. The formation of this structure can significantly increase the contact area between the alumina particles and the bulk membrane, making the isolation membrane structure complete and thus improving the thermal safety of the isolation membrane.

[0234] (3) Taking Example 1, Example 3, Examples 6 to 8, Example 12 and Comparative Examples 1 to 3 as examples, the isolation membranes and positive and negative electrode sheets prepared in the above Examples and Comparative Examples were prepared into battery cells through a lamination process, and insulation breakdown short-circuit resistance tests were performed, and the number of cells that passed the 250V voltage test was counted. The results are shown in Table 3.

[0235] Table 3 Insulation breakdown short circuit test results

[0236]

[0237]

[0238] It can be seen from the test results in Table 3 that, compared with the organic adhesive composite isolation film with PE as the main film and the PE isolation film not coated with an inorganic composite material layer, the isolation film provided by the present invention has good insulation resistance, and the pass rate of the 250V breakdown short-circuit test is more than 95%, while the pass rate of the PE isolation film not coated with an inorganic composite material layer is 79%, and the pass rate of the organic adhesive composite isolation film with PE as the main film does not exceed 90%.

[0239] This indicates that the isolation film provided by the present invention can have higher insulation performance, which is beneficial to improving the yield rate of the battery.

[0240] (4) Taking Example 1, Example 3, Examples 6 to 8, Example 12 and Comparative Examples 1 to 3 as examples, the isolation membranes and positive and negative electrode sheets prepared in the above examples and comparative examples were prepared into battery cells through a lamination process, and then conventional lithium battery processes such as liquid injection, packaging, and formation were carried out. The finished batteries were tested for safety performance, and the results are shown in Table 4.

[0241] 150℃ thermal shock pass rate: tested according to the national standard GB / T18287-2013 method, and the judgment criteria are no leakage, no fire, and no explosion.

[0242] Short circuit pass rate: tested according to the national standard GB / T18287-2013 method, the judgment criteria are no fire, no explosion, and the outer surface temperature is lower than 150℃.

[0243] 10V / 3C overcharge pass rate: tested according to the national standard GB / T18287-2013 method, and the judgment standard is no fire or explosion.

[0244] Table 4 Safety performance test results

[0245]

[0246] It can be seen from the test in Table 4 that, compared with the organic adhesive composite isolation membrane with PE as the main membrane and the PE isolation membrane not coated with an inorganic composite material layer, the battery prepared by the isolation membrane of the present invention has superiority in safety performance testing.

[0247] The isolation film provided by the present invention has a small thermal shrinkage rate at high temperature, which can give the battery good safety performance. When thermal runaway or accidents caused by improper use occur, it can more effectively avoid accidents such as battery fire and explosion.

[0248] In summary, the separator provided by the present invention has good stability and durability at high temperature, and can simultaneously have high peel strength, wettability, ionic conductivity, puncture strength and air permeability, which can ensure that the battery can still operate safely and efficiently under high temperature conditions. The preparation method of the separator is simple and easy to prepare on an industrial scale, and has a good industrial prospect.

[0249] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A separation film, characterized in that: The isolation film includes a main body film and a composite material layer disposed on at least one side surface of the main body film; the composite material layer includes inorganic particles and an inorganic binder; The inorganic binder includes a component with a chemical formula of M2O·nSiO2 and / or a component with a chemical formula of a(Al2O3·mH2O)·bH x ·cH2O aluminum sol, wherein M includes at least one of Na, K and Li, 1≤n≤4; Al2O3·mH2O is hydrated aluminum oxide, H x It is a peptizing agent, and b is smaller than a, c and m.

2. The isolation film according to claim 1, characterized in that: The mass of the inorganic binder is 1% to 35% of the mass of the inorganic particles in the composite material layer.

3. The isolation film according to claim 2, characterized in that: The mass of the component with the chemical formula of M2O·nSiO2 is 1% to 35% of the mass of the inorganic particles in the composite material layer.

4. The isolation film according to any one of claims 1 to 3, characterized in that: The aluminum sol has at least one of the following characteristics: Feature 1: The particle size of the aluminum sol ranges from 5 nm to 200 nm; Feature 2: The pH value of the aluminum sol is 4 to 10; Feature 3: The aluminum sol contains aluminum oxide particles, and the shape of the aluminum oxide particles includes at least one of feather-like, floc-like and fibrous.

5. The isolation film according to any one of claims 1 to 3, characterized in that: The inorganic particles have at least one of the following characteristics: Feature 4: The inorganic particles include at least one of kaolin, boehmite, clay, molecular sieve, Al2O3, SiO2, BaSO4, BaO, MgO, CuO, LiAlO2, ZrO2, Fe2O3, BaTiO3, α-V2O5, PbTiO3, CaSiO3, titanium dioxide, LiF, MgF2, BaF2, TiB2, Mg(OH)2, MoS2, SiC, Si3N4 and carbon nanotubes; Feature 5: The average particle size of the inorganic particles is 10 nm to 5 μm.

6. The isolation film according to any one of claims 1 to 3, characterized in that: The thickness of the isolation film is 2.3 μm to 48 μm; And / or, the thickness of the bulk film is 2 μm to 40 μm; and / or, the bulk membrane comprises at least one of a polymer membrane and a ceramic membrane; And / or, the thickness of the composite material layer is 0.3 μm to 9 μm.

7. A method for preparing a separator according to any one of claims 1 to 6, characterized in that: The following steps are involved: A composite material layer slurry containing the inorganic binder and the inorganic particles is coated on at least one side of the surface of the main film and dried.

8. The preparation method according to claim 7, characterized in that: The composite material layer slurry has at least one of the following characteristics: Feature 6: The solid content of the composite material layer slurry is 2% to 50%; Feature 7: The viscosity of the composite material layer slurry is 10cp to 1000cp.

9. The preparation method according to claim 7 or 8, characterized in that: Drying is carried out at 50°C to 70°C for 2 to 5 minutes.

10. An electrochemical device, characterized in that: The electrochemical device comprises the separator according to any one of claims 1 to 6.

11. A separation film, characterized in that: The isolation film comprises a main body film and a composite material layer arranged on at least one side surface of the main body film; the composite material layer contains crystals formed by an inorganic binder, and the crystals include needle-like whiskers, flaky crystals and spherical crystals.

12. A separation film, characterized in that: The isolation film comprises a main body film and a composite material layer arranged on at least one side surface of the main body film; the composite material layer contains crystals formed by an inorganic binder, and the crystals include needle-shaped whiskers and flake-shaped crystals.

13. A separation film, characterized in that: The isolation film comprises a main body film and a composite material layer arranged on at least one side surface of the main body film; the composite material layer contains crystals formed by an inorganic binder, and the crystals include needle-shaped whiskers and spherical crystals.

14. A separation film, characterized in that: The isolation film includes a main body film and a composite material layer arranged on at least one side surface of the main body film; the composite material layer contains crystals formed by an inorganic binder, and the crystals include at least one of flaky crystals and spherical crystals and needle-shaped whiskers.

Citation Information

Cited By

  • Separator and preparation method therefor, and electrochemical device

    WO2026114317A1